Factors associated with knowledge about ‘Undetectable HIV viral load is Untransmittable’ among Zambian adults on antiretroviral therapy: a mixed method approach - Ngwenya, Fredrick; Makasa, Mpundu (International Journal of Infection Control, 2023)
Background: Knowledge of ‘Undetectable HIV viral load (VL) is Untransmittable’ (U=U) motivates optimal adherence to antiretroviral therapy (ART). Objective: This study assessed factors associated with knowledge about U=U among Zambian people living with HIV on ART. Design: The study used questionnaires and in-depth interviews (IDIs) concurrently between December 2018 and January 2019. Three high volume health facilities, Chilenje, Chipata, and Kalingalinga, were selected. A single proportion of 63.4% of HIV VL suppression (VLS) in Lusaka Province was used to calculate a sample size of 362 respondents. Probability proportional to size procedure was used to apportion the sample to the study sites while a simple random technique was employed in selecting respondents aged 18–59 years and on ART for over 9 months. Stata 14 was used to run descriptive and chi-square statistical analyses. Fifty-five respondents were drawn from 362 respondents for IDIs. The selection was based on varied VL levels. Interviews were audio-recorded, transcribed and analysed thematically, and the findings merged in the discussion. Results: Approximately, 34.5% of the 362 respondents (n = 125) had knowledge about U=U. The VLS status was significantly associated with U=U knowledge (P = 0.01). Discussion: Diverse information sources, symbiotic understanding of VL, and treatment-as-prevention benefits were enablers of acquiring more knowledge about U=U, while inadequate health discussion about VL and congestion and waiting time were barriers. Conclusions: The findings suggest that increased information sharing on the implication of suppressed VL being able to prevent HIV transmission could motivate people living with HIV to adhere to ART, thus sustaining VLS.